Successful conservative management of high output chylothorax in a case of polytrauma - G Sandeep Kumar; Yoga Nagender; T Sneha; Swetha Reddy; Rizwan Ahmed (Wolters Kluwer Medknow Publications, 2019)
Chylothorax, an accumulation of chyle in pleural cavity is a rare complication of pediatric blunt trauma. It could result from damage to or obstruction of thoracic duct. Though rare in incidence chylothorax can lead to significant morbidity and mortality. We report a case of traumatic high output chylothorax following blunt chest trauma in an eleven-year-old boy with h/o fall of ceiling at school. On admission GCS 7/15 with decompensated shock and bilateral hydropneumothorax for which child was intubated, started on inotropes and bilateral ICD placed. On further evaluation was found to have pulmonary contusions, bilateral multiple rib fractures, t4 & t5 vertebral fracture with grade 3 liver laceration. On day 3 child developed high output drain (>1L per day) and was confirmed as chyle on biochemical analysis, which was managed conservatively. The chest tube was removed after drain was completely stopped, he made a full recovery. Initial management of high output chylothorax is thoracic duct ligation or embolization which is typically needed early often within the first few days after diagnosis since conservative strategies are more likely to fail but our case shows that pediatric traumatic high output chylothorax can be successfully managed conservatively.